2004
DOI: 10.1074/jbc.m402953200
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation-induced Stabilization of the Collagen Triple Helix

Abstract: The collagen triple helix is one of the most abundant protein motifs in animals. The structural motif of collagen is the triple helix formed by the repeated sequence of -Gly-Xaa-Yaa-. Previous reports showed that H-(Pro-4(R)Hyp-Gly) 10 -OH (where '4(R)Hyp' is (2S,4R)-4-hydroxyproline) forms a trimeric structure, whereas H-(4(R)Hyp-Pro-Gly) 10 -OH does not form a triple helix. Compared with H-(Pro-Pro-Gly) 10 -OH, the melting temperature of H-(Pro-4(R)Hyp-Gly) 10 -OH is higher, suggesting that 4(R)Hyp in the Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…In contrast the role of 3(S)-hydroxyproline in collagens is not well understood. However, recent studies have shown that 3(S)-hydroxyproline destabilizes the triple helix and that peptides with the sequence Ac-(Gly-3(S)Hyp-4(R)Hyp)10-NH 2 do not form a triple helix (37,38). These studies have suggested the importance of 3(S)Hyp in modulating the stability of basement membrane collagens to allow for the meshwork-like structures they form.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast the role of 3(S)-hydroxyproline in collagens is not well understood. However, recent studies have shown that 3(S)-hydroxyproline destabilizes the triple helix and that peptides with the sequence Ac-(Gly-3(S)Hyp-4(R)Hyp)10-NH 2 do not form a triple helix (37,38). These studies have suggested the importance of 3(S)Hyp in modulating the stability of basement membrane collagens to allow for the meshwork-like structures they form.…”
Section: Discussionmentioning
confidence: 98%
“…[22][23][24] CRPs with Hyp in the Yaa position are more stable than those with Pro, but Hyp in the Xaa position prevents triple-helix formation when the Yaa amino acid is Pro. [24][25][26][27][28][29] In the last decade, we have demonstrated that the stability (or instability) conferred by Hyp derives from the manifestation of previously unappreciated stereoelectronic effects. We did so by installing functional groups at C γ that mediate such effects, as well as reciprocal steric effects ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was thought that a triple helix with 3(S)Hyp residues in the Xaa position would be more stable than one with Pro residues at this position, as Pro does not favor one pucker type (up or down) over the other. Thus, it was a surprise when it was found that peptides with sequences containing long stretches of (3(S)Hyp)-(4(R)Hyp)-Gly do not form stable triple helices (33). However, when Raines and co-workers (20) examined this issue via host guest peptides, specifically, with (Pro-4(R)Hyp-Gly) 3 -3(S)Hyp-4(R)Hyp-Gly-(Pro-4(R)Hyp-Gly) 3 , they found that the presence of 3(S)Hyp residues embedded in the Xaa position of this peptide only decreased the transition midpoint temperature (T m ) value of the triple helix formation by 3°C compared with a peptide with a Pro in the corresponding position.…”
Section: -Oh and H-(4(r)hyp-4(r)hyp-gly)mentioning
confidence: 99%